Schwangerschaft und Stillzeit bei Morbus Crohn - Sonnenberg, Elena; Siegmund, Britta (Aktuelle Ernährungsmedizin, 2024)
Die Erstdiagnose einer chronisch entzündlichen Darmerkrankung (CED) erfolgt oft im jungen Erwachsenenalter. Für viele Patientinnen spielen daher Familienplanung und Schwangerschaft eine zentrale Rolle. Die European Crohn‘s and Colitis Organization (ECCO) hat 2022 eine neue Leitlinie zu Kinderwunsch, Schwangerschaft und Stillzeit herausgegeben [1]. In diesem Beitrag gehen wir auf die neuen Aspekte in Bezug auf Schwangerschaft bei Morbus Crohn ein. Inflammatory bowel disease (IBD) is often diagnosed in young adults. Starting a family is an important step in life and can be further complicated by Crohn’s disease. Therefore, family planning should be discussed with every patient early in the disease course. Counseling about the importance of disease remission and the safety of IBD medication during pregnancy can ameliorate the pregnancy outcome. Active disease during pregnancy can lead to adverse pregnancy outcomes such as preterm birth and low birthweight. To maintain disease remission most therapies should be continued despite the wish to have children. Only a few substances currently used to treat Crohn’s disease are contraindicated during pregnancy and should be stopped before conception. This includes Januskinase (JAK)-inhibitors and Methotrexate. Biologics including anti-TNF-therapy, anti-IL-12/anti-IL-23 and anti-integrin therapies should be continued during pregnancy.
Keywords: Familienplanung; Schwangerschaft; chronisch entzündliche Darmerkrankung; Morbus Crohn; Stillzeit